98.8k views
2 votes
Plzzz help me asap i need the correct answer

Plzzz help me asap i need the correct answer-example-1

2 Answers

2 votes

The Correct answer is A

User TMan
by
5.4k points
7 votes

Answer:

Option A

Explanation:

Given

m=( y_2- y_1)/(x_2-x_1 )

In order to get the equivalent equation, multiplying the denominator x_2-x_1with m.

m(x_2-x_1 )=y_2- y_1

Adding y1 to both sides of equation will give:

m(x_2-x_1 )+ y_1=y_2- y_1+y_1

So the end result will be:

m(x_2-x_1 )+ y_1=y_2

Can also be written as:

y_2=m(x_2-x_1 )+ y_1

Comparing it the given options gives us that Option A is the correct answer.

User Chickeninabiscuit
by
5.2k points